1990
DOI: 10.1001/archotol.1990.01870030095016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nasal Allergic Reactions on the Clearance of Middle Ear Effusion

Abstract: In order to investigate the influence of nasal allergic reactions on the clearance of middle ear effusion, an animal model of nasal allergy and otitis media with effusion was produced in the same guinea pigs simultaneously by passive sensitization with serum of homologous animals containing IgE antibodies (for nasal allergy) and by inoculation of immunocomplex into the tympanic cavity (for otitis media with effusion). Usually, middle ear effusion appeared within 2 to 3 days and disappeared within 7 to 9 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The inflammation continuously interferes with MEE clearance, and an IgE-mediated allergic reaction of mucous membranes lining the nose, nasopharynx, and eustachian tube constitutes one of the factors that are indicative of a chronic state of disease. 3 The present animal experiment demonstrated that AZ administration facilitated the elimination of MEE from the middle ear of guinea pigs in which OME and allergic rhinitis were induced simultaneously. Middle ear effusion developed within 4 days and disappeared spontaneously 10 to 14 days after IC injection in group D animals.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The inflammation continuously interferes with MEE clearance, and an IgE-mediated allergic reaction of mucous membranes lining the nose, nasopharynx, and eustachian tube constitutes one of the factors that are indicative of a chronic state of disease. 3 The present animal experiment demonstrated that AZ administration facilitated the elimination of MEE from the middle ear of guinea pigs in which OME and allergic rhinitis were induced simultaneously. Middle ear effusion developed within 4 days and disappeared spontaneously 10 to 14 days after IC injection in group D animals.…”
Section: Discussionmentioning
confidence: 50%
“…Walker et al 2 reported that a single histamine intranasal provocative challenge in atopic adult individuals resulted in eustachian tube obstruction. In a previous study, 3 it was clearly demonstrated that nasal IgE-mediated allergic reactions interfered with the clearance of middle ear effusion (MEE). The importance of treating allergy has been, therefore, emphasized in patients having both nasal allergy and OME.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of intracellular adhesion molecule‐1 (ICAM‐1) in the nasal mucosa is increased in allergies and, recently, ICAM‐1 has been shown to be a receptor for rhinoviruses, which cause 30% of childhood upper respiratory tract infections (20). Secondary bacterial infection is common following viral colds, and in the presence of negative middle ear pressure and nasopharyngeal colonization with infective organisms, eustachian tube opening may lead to a siphoning effect into the middle ear, precipitating an acute otitis media and a subsequent effusion (21). Rhinitis in childhood is very common and is thought to be frequently infective, with the average child having six to eight viral upper respiratory tract infections per year.…”
Section: Discussionmentioning
confidence: 99%
“…The eustachian tube functions as “a gatekeeper,” limiting access of most substances to the middle ear. 16–18 It has been reported that the mucous membrane of the normal middle ear has few immune‐competent cells. 19,20 Takahashi et al 17 investigated immunocompetent cells in the normal murine middle ear mucosa and found Mac‐1 + cells (macrophages and granulocytes) to be the most predominant cell type, followed in descending order by Lyt‐1 + cells (helper T), IgA + cells, IgG + cells, and IgM + cells.…”
Section: Discussionmentioning
confidence: 99%